1985
DOI: 10.1007/bf00214640
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal growth and differentiation in three hindlimb muscles of the rat

Abstract: The postnatal development, between 0 and 90 days, of three hindlimb muscles and diaphragm of the rat was investigated with respect to fiber types and diameter (histochemistry) and substrate oxidation rates and enzyme activities (biochemistry). The process of muscle fiber differentiation into mature patterns was evaluated by visual classification into 3 or 4 groups having different staining intensities for 3 enzyme-histochemical reactions, enabling 26 fiber types to be distinguished. These exhibited specific si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…It was found that there were differences between V,, and SDH activity in all types of fibre in different muscles in each age group as reported by Goldspink (1969) and Zuurveld et al (1985). However, the authors also found different patterns in different fibre types.…”
Section: Discussionsupporting
confidence: 52%
“…It was found that there were differences between V,, and SDH activity in all types of fibre in different muscles in each age group as reported by Goldspink (1969) and Zuurveld et al (1985). However, the authors also found different patterns in different fibre types.…”
Section: Discussionsupporting
confidence: 52%
“…Also significant higher CK content was observed in BAM-MM. Creatin kinase expression is highly increased during myogenesis and reflects the maturity grade of myofibers 54 , 55 . From the above, we can conclude that both BAM-M and BAM-MM have clear myogenic features but are less mature than adult muscle and that BAM-MM shows more pronounced differentiation than BAM-M.…”
Section: Discussionmentioning
confidence: 99%